The transgenosis main directions in vegetable and melon production: theory and practice - Н. В. Лещук; Л. В. Шаюк; Н. В. Майстер (Plant Varieties Studying and Protection)
The article deals with priority directions of vegetable and melon plants selection. The wide varieties of alien genetic information transferring methods during the transgenic plants creation of vegetable and melon species are grounded. The essence of the new hybrids identification method as genetic engineering products: kind of cabbage, tomatoes, carrots, zucchini, lettuce seed, pea Pisum sativum), common bean, eggplant and capsicum is revealed. The transgenosis main directions of botanical taxa varieties of vegetable and melon plants on condition of the international and national practice holding are proved. The international practice of the state approbation and registration of genetically engineered structures in biological objects (plant varieties) and in their processed products are studied. A monitoring about food and pharmaceutical substances based on genetically modified varieties and hybrids structures of vegetable and melon plants have been held.